2007
DOI: 10.4028/www.scientific.net/kem.348-349.537
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Fatigue Strength of Maraging Steel by Shot Peening

Abstract: Rotating bending fatigue tests up to 108 cycles were carried out to investigate the effects of shot peening on the fatigue strength and the fracture mechanism in an 18 % Ni maraging steel by using shot particles of various sizes or hardness. Fatigue strength was increased markedly by shot peening in the wide region of fatigue life. The S-N curves showed duplex S-N properties because of the transition of fracture origin from the specimen surface in the short life region to the subsurface in the long life one. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The service environment is a major concern when it comes to the fatigue life of maraging steels. Exposure to a humid environment leads to hydrogen embrittlement and acceleration of crack propagation [18][19][20][21][22][23]. Double aging is beneficial in reducing the susceptibility to corrosion fatigue when exposed to humid environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The service environment is a major concern when it comes to the fatigue life of maraging steels. Exposure to a humid environment leads to hydrogen embrittlement and acceleration of crack propagation [18][19][20][21][22][23]. Double aging is beneficial in reducing the susceptibility to corrosion fatigue when exposed to humid environments.…”
Section: Introductionmentioning
confidence: 99%
“…Surface treatments such as shot peening, laser peening or nitriding of maraging steels lead to a complex shape of the SÀ N curve which shows two drops [2,3,[24][25][26]. Shot peening increases the high cycle fatigue life and helps to reduce the sensitivity to humid environments [2,18,24,27]. Laser shock peening helps in delaying both crack initiation and propagation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Surface treatments of superalloy, such as with high intensity pulsed ion beam bombardment [2], surface mechanical attrition treatment [3], laser shock peening [4], and low plasticity burnishing [5], were proven to be capable of the performance to a high extent. Majority of the surface treatments mentioned above often use special steel shot to impact on the surface of materials at high speed, inducing compression and increased density of the surfaces [6][7][8]. In ultrasonic nanocrystalline surface modification (UNSM), the surface is worked with a ball that is mounted on a transducer, which vibrates at a frequency of 20 kHz perpendicular to the surface (z-direction), with potential of two-dimensional (x, y) controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore many studies on fatigue mechanism of the steel have been conducted to improve the fatigue strength. Authors reported that surface treatments like a nitriding and shot peening and formation of reverted austenite were effective to improve the fatigue strength of the steel [2][3][4]. On the other hand, fatigue strength of high strength steels are sensitive not only for notch but also for humidity [5,6].…”
Section: Introductionmentioning
confidence: 99%